A Mapping of the Interconnections Between Religion, Society, and Media in the Age of Artificial Intelligence. - Ikmal Maulana Akbar; Dudi Gamal Firmansyah; Ahmad Sarbini (Busyro: Jurnal Dakwah dan Komunikasi Islam, 2025)
The rapid development of digital media and artificial intelligence (AI) has transformed the way people live and interact in modern society. Nevertheless, the human need for religion as a source of moral and spiritual guidance remains unchanged. This study aims to analyze the conceptual framework of the relationship between religion, society, and media in the era of artificial intelligence through a literature review approach. Data were collected from relevant sources, including academic journals, books, and scholarly articles, and analyzed using a descriptive-analytical method.The results indicate that religion functions as a spiritual and moral compass in guiding the ethical use of media and AI technologies, ensuring that technological progress aligns with values of justice, humanity, and the common good. Meanwhile, media and AI serve as instruments for disseminating religious values and spiritual education, while society acts as the primary agent that interprets and implements these teachings in the digital sphere. Thus, religion, society, and media constitute three interrelated pillars of modern civilization that cannot be separated, even as the world continues to evolve.